Toward a Stakeholder Theory of the Firm: The Saturn Partnership - Kochan, Thomas A.; Rubinstein, Saul A. (Organization Science, 2000)
This paper seeks to engage the organization theory community in contemporary debates over the role of the corporation in American society by using the case of the Saturn corporation to develop and illustrate a stakeholder theory of the firm. One normative and three positive questions are posed for a stakeholder theory: The normative question is: Why should stakeholder models be given serious consideration at this moment in history? The positive questions are: (1) Under what conditions is a stakeholder firm likely to emerge in the United States, (2) what are the critical determinants of performance in a stakeholder firm, and (3) what will determine the sustainability and diffusion of this organizational form in the American environment? The history, design features, and dynamics of the labormanagement partnership at Saturn are used to illustrate and interpret a specific case of employees as stakeholders. Saturn's original mission, governance structure, and internal processes fit the characteristics of a stakeholder firm. Employees establish themselves as influential, definitive stakeholders by using their knowledge to improve organizational performance. The local union likewise contributes to firm performance by organizing workers into a dense social network that contributes to problem solving, conflict resolution, and quality improvement. However, the legal and political environment in which the firm operates produces considerable uncertainty over the sustainability and diffusion of Saturn's features in particular, and the stakeholder organizational form in general. Additional hypotheses and research questions are proposed to continue theory building around the more general model of the stakeholder firm. Researchers are encouraged to take up the analysis of stakeholder models and thereby contribute to the contemporary and future debates over the role of the corporation in American society.